Pola Asuh yang Mendisiplinkan Anak: Seminar Parenting bersama Jemaat HKBP Perumnas II Bekasi - Juniarta Juniarta; Joice Cathryne; Fiorentina Nova (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Discipline is a necessary component of establishing order in a society and must begin at an early age. As the primary unit involved in a child's growth and development, the family plays a critical role in determining a child's discipline. There are numerous misunderstandings about discipline in some community contexts, which eventually result in acts of violence. Inappropriate child discipline will have a negative effect on children for the remainder of their lives. Since the beginning of 2020, the COVID-19 pandemic has compelled the Huria Kristen Batak Protestant church (HKBP) of Perumnas II Bekasi to suspend a number of children's activities, including Sunday School. Although disciplining children is the responsibility of parents, Sunday school activities provide indirect opportunities for youngsters to acquire this skill. With about 103 participants, extension activities in the form of zoominars are conducted online via the Zoom application. The activity was interactive and consisted of material presentation by three speakers, pre- and post-activity polls, quizzes, and questions and answers. In general, the participants' level of understanding increased slightly. Continuing to educate the church community will provide parents with the information and skills necessary to raise children with high self-discipline in the future.